Schisandra chinensis Stem Ameliorates 3-Nitropropionic Acid-Induced Striatal Toxicity via Activation of the Nrf2 Pathway and Inhibition of the MAPKs and NF-κB Pathways - Kim, Eun-Jeong; Jang, Minhee; Lee, Min Jung; Choi, Jong Hee; Lee, Sung Joong; Kim, Sun Kwang; Jang, Dae Sik; Cho, Ik-Hyun (Frontiers in Pharmacology, 2017)
The beneficial value of the stems of Schisandra chinensis (SSC) in neurological diseases is unclear. We examined whether SSC aqueous extract (SSCE) alleviates striatal toxicity in a 3-nitropropionic acid (3-NPA)-induced mouse model of Huntington’s disease (HD). SSCE (75, 150, or 300 mg/kg/day, p.o.) was given daily before or after 3-NPA treatment. Pre- and onset-treatment with SSCE displayed a significant protective effect and pretreatment was more effective as assessed by neurological scores and survival rate. These effects were related to reductions in mean lesion area, cell death, succinate dehydrogenase activity, microglial activation, and protein expression of inflammatory factors including interleukin (IL)-1β, IL-6, tumor necrosis factor-alpha, inducible nitric oxide synthase, and cyclooxygenase-2 in the striatum after 3-NPA treatment. Pretreatment with SSCE stimulated the nuclear factor erythroid 2-related factor 2 pathway and inhibited phosphorylation of the mitogen-activated protein kinase and nuclear factor-kappa B signaling pathways in the striatum after 3-NPA treatment. The gomisin A and schizandrin components of SSCE significantly reduced the neurological impairment and lethality induced by 3-NPA treatment. These results indicate for the first time that SSCE may effectively prevent 3-NPA-induced striatal toxicity during a wide therapeutic time window through anti-oxidative and anti-inflammatory activities. SSCE has potential value in preventive and therapeutic strategies for HD-like symptoms.